2000
DOI: 10.1063/1.481726
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational mode and collision energy effects on proton transfer in phenol cation–methylamine collisions

Abstract: Articles you may be interested inVibrational mode and collision energy effects on reaction of H 2 CO + with C 2 H 2 : Charge state competition and the role of Franck-Condon factors in endoergic charge transfer Vibrational and collisional energy effects in the reaction of ammonia ions with methylamine Mass-analyzed threshold ionization has been used to prepare vibrationally state-selected phenol cations, that were then reacted with methylamine at collision energies ranging from 0.1 to 2 eV. Integral cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…There, too, density of states and adiabaticity factors tend to suppress the higher-energy charge state. We note that for all the polyatomic ion−molecule reactions we have studied we see CT only in cases where the endoergicity is less than 1 eV. ,,, , For this system, the CT endoergicity is only 0.28 eV, hence the substantial CT cross section, but the PT−HT energy difference is 1.1 eV.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…There, too, density of states and adiabaticity factors tend to suppress the higher-energy charge state. We note that for all the polyatomic ion−molecule reactions we have studied we see CT only in cases where the endoergicity is less than 1 eV. ,,, , For this system, the CT endoergicity is only 0.28 eV, hence the substantial CT cross section, but the PT−HT energy difference is 1.1 eV.…”
Section: Discussionmentioning
confidence: 76%
“…For the exoergic ME and HT reactions, the distributions are not significantly different for the reaction of vibrationally excited reactants. An absence of significant vibrational effects on recoil velocity is typical for exoergic reactions of polyatomic ions, 1,[15][16][17][18][19][20][21][22][23] and the reasons for the absence have been discussed recently. 24 The effects of vibration on the endoergic CT channel are discussed below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the experimental study found that NO 2 + vibrational excitation, particular bending, results in substantial changes in the product recoil dynamics at high collision energies, leading to a more forward-scattered velocity distribution than for the ground state. In past studies of vibrational effects on product recoil in ion reactions, we have seen insignificant effects on product recoil, even for reactions where vibration strongly affects reactivity. , Lack of vibrational effects on recoil is not surprisingenergy is likely to be scrambled in reactive collisions, and reactant E vib is typically only a small fraction of the total energy available to products, particularly at high E col . As might be expected, the exception has been for endoergic reactions near threshold, where E vib is a significant fraction of the energy available to products. , The present reaction is more than 2.5 eV exoergic, such that the bending vibrations contribute <3.5% of the available energy at high E col .…”
Section: Summary Of the Experimental Results And Properties Of The Sy...mentioning
confidence: 91%
“…In past studies of vibrational effects on product recoil in ion reactions, we have seen insignificant effects on product recoil, even for reactions where vibration strongly affects reactivity. 5,[7][8][9][10][11][12][13][14][15][16][17] Lack of vibrational effects on recoil is not surprisingsenergy is likely to be scrambled in reactive collisions, and reactant E vib is typically only a small fraction of the total energy available to products, particularly at high E col . As might be expected, the exception has been for endoergic reactions near threshold, where E vib is a significant fraction of the energy available to products.…”
Section: Summary Of the Experimental Results And Properties Of The Sy...mentioning
confidence: 99%